Career motives according to degree of religiosity among Jewish students in Israel. Issue 2 (14th March 2020) - Sharabi, Moshe; Polin, Brian A
ABSTRACT: Members of Israel's Jewish population self-identify along religious lines as ultra-orthodox, religious, traditional, or secular. Adherents of each group maintain different lifestyles and different social, political and economic values. This unique study attempts to reveal the differing intra-state career motives among these sub-groups. The global research project GUESSS (Global University Entrepreneurial Students' Spirit Survey) included 995 Israeli students, who were asked about their career motives. The findings reveal that there is a very high similarity between ultra-orthodox and religious on one hand and between traditional and secular on the other hand, regarding career motives. Ultra-orthodox and religious had a significantly lower motive for autonomy and control, for a stimulating job and for realizing dreams and creativity than traditional and secular. Gender and age do not affect the motives, while military service and family status have a significant effect on the motive for autonomy and control.